Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To determine whether the statement [tex]\(\cos(-x) = -\cos(x)\)[/tex] is true for all values of [tex]\(x\)[/tex], let's consider the nature of the cosine function.
The cosine function, [tex]\(\cos(x)\)[/tex], has a specific property known as even symmetry. This property means that the cosine of a negative angle is equal to the cosine of the corresponding positive angle:
[tex]\[ \cos(-x) = \cos(x) \][/tex]
To verify this, let's check the identity at specific values of [tex]\(x\)[/tex]:
1. When [tex]\( x = 0 \)[/tex]:
[tex]\[ \cos(-0) = \cos(0) \][/tex]
[tex]\[ 1 = 1 \][/tex]
This matches [tex]\(\cos(0) = \cos(0)\)[/tex], not [tex]\(-\cos(0)\)[/tex].
2. When [tex]\( x = \frac{\pi}{2} \)[/tex] (90 degrees):
[tex]\[ \cos\left(-\frac{\pi}{2}\right) = \cos\left(\frac{\pi}{2}\right) \][/tex]
[tex]\[ 0 = 0 \][/tex]
This matches [tex]\(\cos\left(\frac{\pi}{2}\right) = \cos\left(\frac{\pi}{2}\right)\)[/tex], not [tex]\(-\cos\left(\frac{\pi}{2}\right)\)[/tex].
3. When [tex]\( x = \pi \)[/tex] (180 degrees):
[tex]\[ \cos(-\pi) = \cos(\pi) \][/tex]
[tex]\[ -1 = -1 \][/tex]
This matches [tex]\(\cos(\pi) = \cos(\pi)\)[/tex], not [tex]\(-\cos(\pi)\)[/tex].
From this analysis of specific values, we see that the cosine of [tex]\( -x \)[/tex] equals the cosine of [tex]\( x \)[/tex], not the negative of it. Thus, the statement [tex]\(\cos(-x) = -\cos(x)\)[/tex] is false for all values of [tex]\(x\)[/tex].
Hence, the correct answer is:
B. False
The cosine function, [tex]\(\cos(x)\)[/tex], has a specific property known as even symmetry. This property means that the cosine of a negative angle is equal to the cosine of the corresponding positive angle:
[tex]\[ \cos(-x) = \cos(x) \][/tex]
To verify this, let's check the identity at specific values of [tex]\(x\)[/tex]:
1. When [tex]\( x = 0 \)[/tex]:
[tex]\[ \cos(-0) = \cos(0) \][/tex]
[tex]\[ 1 = 1 \][/tex]
This matches [tex]\(\cos(0) = \cos(0)\)[/tex], not [tex]\(-\cos(0)\)[/tex].
2. When [tex]\( x = \frac{\pi}{2} \)[/tex] (90 degrees):
[tex]\[ \cos\left(-\frac{\pi}{2}\right) = \cos\left(\frac{\pi}{2}\right) \][/tex]
[tex]\[ 0 = 0 \][/tex]
This matches [tex]\(\cos\left(\frac{\pi}{2}\right) = \cos\left(\frac{\pi}{2}\right)\)[/tex], not [tex]\(-\cos\left(\frac{\pi}{2}\right)\)[/tex].
3. When [tex]\( x = \pi \)[/tex] (180 degrees):
[tex]\[ \cos(-\pi) = \cos(\pi) \][/tex]
[tex]\[ -1 = -1 \][/tex]
This matches [tex]\(\cos(\pi) = \cos(\pi)\)[/tex], not [tex]\(-\cos(\pi)\)[/tex].
From this analysis of specific values, we see that the cosine of [tex]\( -x \)[/tex] equals the cosine of [tex]\( x \)[/tex], not the negative of it. Thus, the statement [tex]\(\cos(-x) = -\cos(x)\)[/tex] is false for all values of [tex]\(x\)[/tex].
Hence, the correct answer is:
B. False
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.